Pengaruh Karakteristik Individu dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada CV. Medan Promotion - Alya Novianti; Taufiq Risal (Universitas Katolik Widya Karya Malang, 2023)
This research aims to determine the influence of individual characteristics and work environment on employee performance at CV. Medan Promotions. The type of research used in this research uses quantitative research. The number of samples used in this research was 61 respondents. The testing techniques used in research are research instrument tests, descriptive statistical tests, assumption tests, multiple linear regression tests, hypothesis tests. The results of the research show that individual characteristic variables do not have a positive and significant effect on employee performance, while work environment variables have a significant and positive effect on employee performance at CV. Medan Promotions. Simultaneously, it can be seen that individual characteristic variables and the work environment have a positive and significant effect on employee performance at CV. Medan Promotions.